Challenging the chain governing the automated exchange and processing of business information - Bharosa, Nitesh; Wijk, Remco van; Winne, Niels de; Janssen, Marijn 1972- (IOS Press, 2015)
What is digital business reporting? Why do we need it? And how can we improve it? This book aims to address these questions by illustrating the rise of system-to-system information exchange and the opportunities for improving transparency and accountability. Governments around the world are looking for ways to strengthen transparency and accountability without introducing more red tape, which is a source of growing frustration and costs for businesses. In 2004, the Ministry of Finance and the Ministry of Justice in the Netherlands started to investigate the potential of XBRL (eXtensible Business Reporting Language) as a uniform data standard for business-to-government information exchange. In 2006, there was a comprehensive architecture for Standard Business Reporting (SBR), including the requirements for the information infrastructure. One year later the first reports in XBRL were successfully delivered to the Tax and Customs Administration and the Chamber of Commerce via a secure infrastructure. Today, millions of business reports are being exchanged using SBR. As a solution, SBR empowers organisations to present a cohesive explanation of their business operations and helps them engage with internal and external stakeholders, including regulators, shareholders and creditors.Challenging the chain describes the journey of SBR from challenge to solution. Specialists in the field - flanked by academics - provide detailed insights on the challenges actors faced and the solutions they achieved. In its versatility, this book exemplifies the necessary paradigm shifts when it comes to such large-scale public-private transformations. Policy makers, managers, IT specialists and architects looking to engage in such transformations will find guidance in this book
"Published online with Open Access by IOS Press" (Impressum)
Open Access funded by TU Delft Open Access Fund
Keywords: Information technology